Reviews and notices - Elisabeth Ahlsén; Mats Mobärg; Norman Vance; Stephen Medcalf; Jeremy Lane; Britt-Marie Kylander; Olof Eriksson; Marie-Rose Blomgren; Gunnar Magnusson; Gustav Korlén; Evald Johansson; Birgit Stolt; et al. (Moderna Språk)
Includes the following reviews: